Scientific Approach based Guided inquiry with Smart Messages to Improve Observation Skill and Learning Outcome - BUDIATI, HERNI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
The aim of this research is to improve the observation skill and the learning achievement on Human Motion System, which is taught at grade 8. The research was Classroom Action Research, using Scientific approach based on guided inquiry using smart messages. The participants were 29 students  of Class VIIIE of SMP Negeri 22 Surakarta in 2016. Data was collected by observing learning process and doing test of students' achievement. The instruments of the research consists of lesson plans, observation sheet and guidelines of observation skill, and tests as an assesment of kognitive knowledge. The procedures in this classroom action research adopted the Kemmis and Taggart model which consist of plan, action, observation, and reflection. Qualitative data were analyzed descriptively. The research showed an increase of observation skills and learning achievement of participants students through the application of scientific approach by guided  inquiry using smart messages.